Impact of Multi-Functional Sit-to-Stand Device on Balance and Functional ability in the elderly people - Punitha, Punitha; GeevaKamalraj, GeevaKamalraj (Journal of Neonatal Surgery, 2025)
People's functional ability and balance deteriorate with age, making daily chores more difficult and increasing the chance of falling. Occupational therapy plays a crucial role in enhancing mobility, stability, functional mobility and overall quality of life among the elderly people. This study aims to find out the efficacy of Multi-functional sit-to-stand device on improving balance and functional abilities in older adults. Methods: An Experimental study was conducted with 60 elderly participants, who were divided .into a control group (conventional occupational therapy) and an experimental group (multi-functional sit-to-stand devices). The effectiveness of interventions was assessed using the Time Up and Go (TUG) test, BERG Balance Scale, and 30C Chair test. Pre- and post-test assessments were conducted for both groups, and statistical analysis was performed to determine the significance of improvements. Results: The experimental group demonstrated significantly greater improvement compared to the control group in all three outcome measures. The mean TUG test score improved from 13.75 to 11.57 seconds (p = 0.000**), BERG Balance Scale score increased from 43.39 to 48.97 (p = 0.000**), and 30C Chair test repetitions increased from 9.52 to 14.32 (p = 0.000**). The control group also showed improvements, but the magnitude was significantly lower. Conclusion: The findings suggest that integrating multi-functional sit-to-stand devices into occupational therapy programs can be highly effective in enhancing mobility, balance, and functional independence in elderly individuals. These devices offer along with conventional therapy for reducing fall risk and improving quality of life in aging populations.